Inter-provincial trade in Argentina: Financial flows and centralism - Pedro Elosegui; Marcos Herrera; Jorge Colina (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2021)
This paper is part of a broader agenda and constitutes a first step to empirically understand the main determinants of the inter-provincial trade in Argentina. We use a novel database of regional trade flows between the 24 Argentinean provinces for 2017. Using a structural gravity model and novel econometric techniques we analyze the main variables influencing trade between the provinces. In addition to the traditional variables of the canonical gravity model we add some variables of interest that ca possible affect trade between sub national jurisdictions. With an especial focus in financial flows we analyze the impact of co-participation transfers, income distribution and household's payment methods, among other variables that may be correlated with formal trade. Additionally, we analyze the potential impact of trade concentration in the Autonomous City of Buenos Aires (CABA) and Buenos Aires. Trade flows are analyzed considering both, origin and destination. The results indicate that national transfers from the redistribution federal arrangement are an important determinant of inter provincial trade generating relevant (and negative in the origin) spillover effects between the provinces. Also, the concentration in CABA and Buenos Aires discourages inter-provincial trade.
Keywords: R10; F14; C21; 330; Gravity Model; Spatial Interactions; Redistribution Federal Arrangement